Microstructure, texture and orientation dependent flow behavior of hot rolled and annealed ternary Ni-16Cr-16Mo, Ni-16Cr-4W and Ni-16Cr-8Fe alloys - Mehta K.K.; Mukhopadhyay P.; Mandal R.K.; Singh A.K. (My University, 2025)
Present work describes a correlation among microstructure, texture and mechanical properties anisotropy of ternary Ni-16Cr-16Mo, Ni-16Cr-4W and Ni-16Ce-8Fe alloys in hot rolled and annealed condition. The evolution of microstructures of the alloys has been explained based on stacking fault energy and presence of texture components in the material. The alloys Ni-16Cr-16Mo, Ni-16Cr-4W and Ni-16Cr-8Fe exhibit low, moderate and high values of in-plane anisotropy, respectively. The anisotropy index values of alloys Ni-16Cr-4W, Ni-16Cr-8Fe and Ni-16Cr-16Mo are moderate, high and moderate, respectively. The overall intensity and extent of homogeneity of the {111}-fiber have marked influence on both the σYS and uniform elongation values. The alloys reveal the presence of two slopes in true plastic stress-strain curves and follow typical Ludwigson relation. The deformation behavior in low strain regime is associated with formation of uniform and finely spaced slip lines within the grains as a result of very small fraction of strain localization. On the other hand, main attributes of high strain regime are penetration of a few coarse slip lines across the grain boundaries along with large volume fractions of deformation twins and strain localization. The overall nature of differential curves of all the alloys is quite different although these curves consist of typical three stages (I, II and III) of work hardening. The nature of differential curves indicates different deformation mechanisms associated with these alloys during uniform elongation. Uniform elongation values of the alloys have been explained based on dynamic recovery coefficient using Kocks-Mecking-Estrin analysis. © 2015 Elsevier Inc.